Exploring the Impact of Digitalized Learning and Teaching Systems on the Big Five Personality Traits - Arslan, Ezgi Yıldırım; Yıldırım, Osman; KAYNAŞ, TAYFUN; Atanasov, Koycho (Springer Science and Business Media Deutschland GmbH, 2023)
As information technologies develop, educational technology tools develop and differentiate in parallel. Effective and easily applicable technological learning methods have great effects on both learning styles and teaching styles and even transform them. Keeping in mind the contributions of learning technologies to the learning environment, this chapter aimed to examine the effects of flipped learning styles on students’ personality traits. For this purpose, research data were collected by applying a face-to-face survey to 362 higher education students who accepted voluntary participation, and the obtained data were evaluated and interpreted with the help of statistical analysis. According to the analysis findings, important relationships emerged between the sub-dimensions of the flipped learning sub-dimensions of a model known as the big five models. For example, a flexible environment was found to be explained by 12.9% of personality traits, conscientiousness, extraversion, and openness to experience dimensions. One aspect that unifies this research is that educators’ attention is drawn to the points where the development of information technologies forces them to go beyond the classical classroom face-to-face teaching methods.
▪️ Part of the Contributions to Management Science book series (MANAGEMENT SC.)
Keywords: Big Five; Digitalized Learning; Flipped Learning; Personality Traits